Issue of Tokens Referring to The Epidemic: A Way to Obtain Funds for Business Purposes or To Fight the Coronavirus? - Agnieszka WIS (Communications of International Proceedings, 2021)
The economic situation during the coronavirus epidemic left many companies in a difficult financial situation. Each company had to look for an appropriate form of funding and in the digital space for startups, obtaining financing using Initial Coin Offering is a good option. Such financing means issuing tokens that are bought by investors and in this way financial funds are transferred to the company. The time of the pandemic caused many token-issuing projects to refer to the coronavirus, which stirred up a lot of controversy. The aim of this article is to evaluate the issue of tokens relating to the epidemic. The research question contained in the article is: what are the goals of issuing tokens referring to the epidemic? The research hypothesis contained in the article is: projects issuing tokens referring to the epidemic are used to obtain funds for the implementation of business goals while taking into account social functions. The evaluation and analysis of 39 tokens allowed to achieve the purpose of the article, and also allowed to answer the research question that the projects mainly focus on achieving business goals. The research hypothesis has not been fully confirmed because not all of the analyzed projects perform social functions.
Keywords: Initial Coin Offering; Tokens Referring to The Epidemic; Business Goals; Social Functions.